Experimental study on the effect of grouting volume on the tensile performance of offset semi-grouted couplers. (10th October 2022) - Yin, Fenfang; Yin, Shiping; Qin, Tianhao; Wang, Boxue; Zhang, Linglei; Yang, Ning
Highlights: The effect of grouting amount of the semi-grouted sleeve connections was investigated. Effects of various factors were revealed (such as bar diameter, grouting amount). The grouting amount influences the bearing capacity and stiffness of the connection. The model of effective bond length and the formula of maximum bond stress are put forward. Abstract: Research results have shown that the mechanical properties of sleeve grouting connections are related to the diameter of the rebar, the sleeve, the grout, the temperature and the loading method, but research on the factor of grout volume needs to be further developed. Therefore, this paper considers the effects of three grouting volumes (50%, 75% grouting and 100% full grouting) on the tensile properties of the joint under the offset condition of the rebar. A total of 22 uniaxial tensile tests on semi-grouted steel sleeve connection specimens were carried out, mainly to study the damage morphology, load-displacement relationship, stiffness and the strain change law on the surface of the rebar and the sleeve under different grouting amount, etc. The stress mechanism of the specimens in the tensile condition was analysed, and the effective bond length calculation model was proposed with reference to the steel-concrete bond strength research theory, and the formula for calculating the maximum bond stress related to the effective anchorage length was obtained. Studies have shown that the grouting amount affects the load bearing capacity and stiffness, and that the quality of the specimen joint is reliable when the grouting volume reaches more than 75% of the design grouting volume.